(untitled) (Castilla. Estudios de Literatura, 2020)
This paper analyses the Fábula de Faetón by Conde de Villamediana from the rhetoric. Its purpose is to establish a structure consistent with the compositional postulates in the Spanish Golden Age, which must include an arrangement of the text depending on the rhetoric. This paper differs from previous structural analyzes, whose base is a certain architectural idea.